Low incidence of hepatitis C virus among prisoners in Scotland. (1st March 2013) - Taylor, Avril; Munro, Alison; Allen, Elizabeth; Dunleavy, Karen; Cameron, Sheila; Miller, Laura; Hickman, Matthew
Abstract Aims To estimate hepatitis C virus (HCV) incidence and HCV risk among Scottish prisoners. Design National sero‐behavioural survey; dried blood spots were collected in order to identify recent HCV infections (i.e. HCV antibody‐negative and HCV polymerase chain reaction (PCR)‐positive). Setting All 14 closed prisons in Scotland. Participants A total of 5187 prisoners responded to the survey (79% of available prisoners on survey days) comprising 5076 individuals (after removing incomplete returns and participants surveyed in more than one prison); 95% men, 32% (1625) reported an injecting history (PWID) and median sentence of 9.5 months. HCV antibody samples were available for 4904 participants; there was sufficient sera for HCV PCR for 2446 prisoners who had been in prison for at least 75 days. Measurements The estimate of in‐prison recent infections is based on prisoners incarcerated for a sufficient period, i.e. at least 75 days, so that recent infections could be attributed to prison. Findings Overall HCV prevalence was 19%; 53% among people who reported an injecting history and 3% among other prisoners. Three recent infections probably acquired in prison were detected. None of the cases reported injecting during their current sentence or any other potential exposure. Estimated incidence was 0.6–0.9% overall and 3.0–4.3% among PWID (assuming all infections acquired through injecting). Fifty‐seven per cent (929) of PWID were receiving opiate substitution treatment (OST) at the time of the survey. Of all prisoners, 2.5% and 8% of PWID reported injecting during their current period of incarceration. Conclusion The low incidence of HCV infections in Scottish prisons is due most probably to the low occurrence of in‐prison injecting and high coverage of OST. Low HCV risk can be achieved in prisons without necessarily introducing needle exchange programmes, but close monitoring of risk behaviours is essential. If risk increases, provision of needle exchange should be considered.